INDICATORS OF THE PHYSICAL CONDITION AND DISEASE STRUCTURE IN THE ELDERLY - Погодина, Вера Александровна; Бабенко, Анатолий Иванович; Половникова, Анастасия Владимировна; Бабенко, Евгений Анатольевич (Medicine in Kuzbass, 2019)
The lack of age-specific standards of physiometric parameters in the adult population does not allow an adequate assessment of physical health.Objective. The objective is analyzing physiometric indicators of health status and prevalence of pathology among the elderly people.Material and methods. Parameters of physical health and presence of diseases from statistical registration forms (N 025/u-04; N 025-12/u; N 131/u) for 2015-2016 in Novosibirsk were estimated. A sample study of 300 patients aged 60-70 years was conducted. Physiometric health indicators of this group were compared with the data of generally accepted classifications for adults without regard to age.Results. There were from 17.0 % to 51.0 % of the elderly population with a normal body type and average parameters of arterial blood pressure, heart rate, respiratory movements accepted in the Russian Federation. At the same time, people of this age of asthenic and hypersthenic body type were revealed, respectively, 23.0 % and 46.0 %. The share of the contingent, which had the bradycardia was 13.9 %, while tachycardia was 38.7 %. High levels of arterial blood pressure were noted in 83.0 % of the subjects. Persons 60-70 years with bradypnea were determined by 16.3 % and tachypnea was established in 32.7 %. The most common were diseases of the circulatory system – 24.5 % (coronary heart disease – 14.7 %), pathology of the genitourinary system – 24.5 % (non-inflammatory diseases of the female genital organs – 16.7 %), reaction to severe stress, adaptation disorders – 23.5 %. All patients in this age group had severe chronic pathology (47.0 %) and light (27.7 %) degree of severity, and need of dynamic observation of the condition.Conclusion. The established parameters of the physical state of health and the presence of pathology in elderly people indicate large amplitude of the population spread, which suggests the development of appropriate age standards for this contingent in order to determine the relevance of diagnostic, treatment and prevention and rehabilitation measures.
Keywords: physical indicators; pathology; contingent of 60-70 years